Pharmacotherapeutic strategies for standard treatment-resistant psoriasis. (4th March 2019) - Heath, Michael S.; Kolli, Sree S.; Dowling, Jessica R.; Cline, Abigail; Feldman, Steven R.
ABSTRACT: Introduction : Psoriasis management includes a variety of treatments including localized therapies and systemic treatments; however, many patients report inadequate clinical response and resistance to therapy. Currently there is no treatment algorithm that incorporates effective strategies to tackle the various barriers leading to resistance. Areas covered : The authors evaluate the scope of resistance, the reasons it occurs, and provide the reader with strategies for overcoming resistance in both localized and systemic therapies for psoriasis. Expert opinion : Refractory psoriasis involves modifiable and non-modifiable factors that warrant different approaches to maximize clinical response. Treatment-resistance to topical therapies may be due to poor adherence. Improving adherence involves incorporating patients' treatment preferences, improving the physician-patient relationship, and simplifying treatment regimens. Treatment-resistance to systemic therapies can be due to non-adherence but can also be due to ineffective dosing, development of anti-drug antibodies, and severe disease that necessitates multiple drugs. After addressing non-adherence, strategies to maximize systemic therapies include increasing the dosage, combining treatments, drug switching and incorporating pharmacogenetics.